Energy dissipation dataset for reversible logic gates in quantum dot-cellular automata - Ali Newaz Bahar; Mohammad Maksudur Rahman; Nur Mohammad Nahid; Md. Kamrul Hassan (Data in Brief, 2017)
This paper presents an energy dissipation dataset of different reversible logic gates in quantum-dot cellular automata. The proposed circuits have been designed and verified using QCADesigner simulator. Besides, the energy dissipation has been calculated under three different tunneling energy level at temperature T=2 K. For estimating the energy dissipation of proposed gates; QCAPro tool has been employed.